All Transition Metal Selenide Composed High‐Energy Solid‐State Hybrid Supercapacitor. Issue 20 (20th April 2022) - Shinde, Pragati A.; Chodankar, Nilesh R.; Abdelkareem, Mohammad Ali; Patil, Swati J.; Han, Young‐Kyu; Elsaid, Khaled; Olabi, Abdul Ghani
Abstract: Transition metal selenides (TMSs) have enthused snowballing research and industrial attention due to their exclusive conductivity and redox activity features, holding them as great candidates for emerging electrochemical devices. However, the real‐life utility of TMSs remains challenging owing to their convoluted synthesis process. Herein, a versatile in situ approach to design nanostructured TMSs for high‐energy solid‐state hybrid supercapacitors (HSCs) is demonstrated. Initially, the rose‐nanopetal‐like NiSe@Cu2 Se (NiCuSe) positive electrode and FeSe nanoparticles negative electrode are directly anchored on Cu foam via in situ conversion reactions. The complementary potential windows of NiCuSe and FeSe electrodes in aqueous electrolytes associated with the excellent electrical conductivity results in superior electrochemical features. The solid‐state HSCs cell manages to work in a high voltage range of 0–1.6 V, delivers a high specific energy density of 87.6 Wh kg −1 at a specific power density of 914.3 W kg −1 and excellent cycle lifetime (91.3% over 10 000 cycles). The innovative insights and electrode design for high conductivity holds great pledge in inspiring material synthesis strategies. This work offers a feasible route to develop high‐energy battery‐type electrodes for next‐generation hybrid energy storage systems. Abstract : The implication of the present work is the utilization of highly conductive, battery‐type metal selenides as positive and negative electrodes for hybrid supercapacitors (HSCs). The HSCs comprising NiSe@Cu2 Se (NiCuSe) as a positive electrode and FeSe as a negative electrode deliver a high specific energy density of 87.6 Wh kg −1 at a specific power density of 914.3 W kg −1 .